Severity of anar butterfly, Deudorix epijarbas damage to pomegranate in Kashmir - Din, Sajad Mohi Ud; Zaki, F A; Wani, R A; Ahmad, M Jamal; Sofi, M A (Indian Journal of Plant Protection, 2020)
Survey on the pest severity of pomegranate fruit borer (Deudorix epijarbas) was conducted during 2011 and 2012 at three places each in districts of Srinagar, Budgam and Ganderbal. The data pooled for 2011 and 2012 revealed that the highest mean pest severity (6.91%) was recorded in Srinagar, followed by Budgam (5.56%), while comparatively low mean severity (5.08%) of pest was recorded in Ganderbal. The pest started its activity in the 2nd fortnight of May and attained its peak in the month of August in Srinagar, Budgam and Ganderbal. Among different locations of Srinagar, the highest mean pest severity (7.97%) was recorded at Nishat, while the lowest pest severity (6.07%) was recorded at Botakadal. Similarly, in district Budgam, the highest pest severity (6.23%) was recorded at Soibough, and the lowest pest severity (4.78%) was recorded at Chadoora locality. Observations from district Ganderbal revealed that the highest pest severity (5.83%) was recorded at Raipur, whereas, the lowest mean pest severity (4.34%) was recorded from Wussan locality. In the present study as many as 7 caterpillars were found in a single fruit.